Banana split - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Cryopreservation of Musa germplasm By B Panis & Nguyen Tien Thinh. Edited by J V Escalant & S Sharrock, published by the International Network for the Improvement of Banana and Plantain (INIBAP) with CTA support, INIBAP Technical Guidelines 5, 2001. 44 p